2022
DOI: 10.1002/cam4.5285
|View full text |Cite
|
Sign up to set email alerts
|

A novel integrated biomarker index for the assessment of hematological responses in MPNs during treatment with hydroxyurea and interferon‐alpha2

Abstract: Background Conventional cytoreductive therapy for patients with chronic Philadelphia‐negative myeloproliferative neoplasms (MPNs) includes hydroxyurea (HU), interferon‐alpha2 (IFN), and anagrelide. HU is worldwide the most used cytoreductive agent, which lowers elevated blood cell counts within days in the large majority of patients. However, some patients may experience rebound cytosis when HU is reduced due to cytopenia, thereby potentially giving rise to fluctuating cell counts during therapy. Such rapid os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In the DAHLIA, PROUD-PV and Myeloproliferative Disorders Research Consortium 112, HU was shown to reduce JAK2 V617F VAF in the first year but then rebound and continue to rise after 2 years, such that the VAF increase over 5 years was roughly 1.2% per year ( Table 3 ). 60 , 67 , 77 Similarly, the VAF rise in the BAT arm in RESPONSE-1 was 1.2% at week 32, and in RESPONSE-2, was 1.2% per year over the 5-year trial. 3 , 69 In the LOW-PV study, where phlebotomy alone was compared with phlebotomy plus low-dose ropeginterferon, the increase in JAK2 V617F VAF in the phlebotomy arm was 1% over 12 months ( Table 3 ).…”
Section: Evaluating Jak2 V617f Vaf In P...mentioning
confidence: 91%
“…In the DAHLIA, PROUD-PV and Myeloproliferative Disorders Research Consortium 112, HU was shown to reduce JAK2 V617F VAF in the first year but then rebound and continue to rise after 2 years, such that the VAF increase over 5 years was roughly 1.2% per year ( Table 3 ). 60 , 67 , 77 Similarly, the VAF rise in the BAT arm in RESPONSE-1 was 1.2% at week 32, and in RESPONSE-2, was 1.2% per year over the 5-year trial. 3 , 69 In the LOW-PV study, where phlebotomy alone was compared with phlebotomy plus low-dose ropeginterferon, the increase in JAK2 V617F VAF in the phlebotomy arm was 1% over 12 months ( Table 3 ).…”
Section: Evaluating Jak2 V617f Vaf In P...mentioning
confidence: 91%